Porphyromonas gingivalis lipopolysaccharide affects oral epithelial connections via pyroptosis - Yuyang Li; Baosheng Li; Yujie Liu; Haoyang Wang; Mengxiao He; Yanqun Liu; Yidan Sun; Weiyan Meng (Journal of Dental Sciences, 2021)
Background/purpose: Pyroptosis is a form of programmed cell death dependent on the activation of caspase-1. Porphyromonas gingivalis (P. gingivalis) is a major pathogenic bacterium in periodontitis and its lipopolysaccharide (LPS) can trigger inflammation. However, whether P. gingivalis-LPS affects epithelial connections or triggers pyroptosis in the gingival epithelium is unknown. Materials and methods: Gingival samples from human donors were collected and the expression levels of E-cadherin, nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), caspase-1/4/5, interleukin (IL)-18, and IL-1β were examined. P. gingivalis-LPS was injected into rat gingival sulcus to establish gingivitis models, and the expression levels of E-cadherin, NLRP3, caspase-1/11, IL-18, and IL-1β were compared via immunohistochemistry. The mRNA levels of E-cadherin, caspase-1, IL-18, and IL-1β were evaluated in oral mucosa epithelial cells (OMECs) and rat gingival tissues. Results: In the present study, NLRP3 (p < 0.01), caspase-1 (p < 0.01), caspase-4 (p = 0.044), and IL-18 (p = 0.036) expression was greater in the human inflammatory gingival samples, whereas E-cadherin (p = 0.045) had the opposite presentation. Gingivitis models were successfully established in rats with the injection of P. gingivalis-LPS. NLRP3 (p = 0.015), caspase-1 (p < 0.01), caspase-11 (p < 0.01), and IL-18 (p = 0.041) were upregulated, whereas E-cadherin (p = 0.038) expression was decreased. Furthermore, E-cadherin mRNA was decreased while caspase-1, IL-18, and IL-1β mRNA levels were increased. The addition of a caspase-1 inhibitor reversed the expression changes. Conclusion: P. gingivalis-LPS may effectively destroy the epithelial connection by triggering pyroptosis.